2013
DOI: 10.1002/ajh.23564
|View full text |Cite
|
Sign up to set email alerts
|

Associations between allergies and risk of hematologic malignancies: Results from the VITamins and lifestyle cohort study

Abstract: Immune dysregulations associated with allergies may affect cancer cell biology but studies on the relationship between allergies and risk of hematologic malignancies (HM) yielded inconsistent results. Herein, we used the VITamins and Lifestyle (VITAL) cohort to examine this association. From 2000–2002, 66,212 participants, aged 50–76, completed a baseline questionnaire on cancer risk factors, medical conditions, allergies, and asthma. Through 2009, incident HMs (n=681) were identified via linkage to the Survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
(33 reference statements)
1
25
0
1
Order By: Relevance
“…There have been several investigations regarding definition and measurement of allergies and the subtypes of HM assessed, however, an inverse association with history of allergies has been reported for HM as a group [4], lymphoma overall [5,6], Hodgkin's lymphoma (HL), Non Hodgkin lymphoma (NHL) [7][8][9][10], Acute Lymphoblastic Leukemia (ALL) [11,12], and multiple myeloma (MM) [13] (Table 1) [14]. The study indicates a moderately increased risk of HMs in women but not in men with a history of allergies to airborne allergens, especially to plants, grass, or trees.…”
Section: Allergy and Hematologic Malignanciesmentioning
confidence: 97%
“…There have been several investigations regarding definition and measurement of allergies and the subtypes of HM assessed, however, an inverse association with history of allergies has been reported for HM as a group [4], lymphoma overall [5,6], Hodgkin's lymphoma (HL), Non Hodgkin lymphoma (NHL) [7][8][9][10], Acute Lymphoblastic Leukemia (ALL) [11,12], and multiple myeloma (MM) [13] (Table 1) [14]. The study indicates a moderately increased risk of HMs in women but not in men with a history of allergies to airborne allergens, especially to plants, grass, or trees.…”
Section: Allergy and Hematologic Malignanciesmentioning
confidence: 97%
“…MPNs were grouped along with other myeloid malignancies based on the WHO classification system [1]. No significant associations between allergies and myeloid neoplasms were identified [78].…”
Section: Allergiesmentioning
confidence: 99%
“…The VITamins And Lifestyle cohort study was used to investigate the role of allergies in the development of haematological malignancies [78]. MPNs were grouped along with other myeloid malignancies based on the WHO classification system [1].…”
Section: Allergiesmentioning
confidence: 99%
“…[5][6][7][8][9] Over the past few decades, substantial amounts of epidemiologic and clinical data have described the associations between allergic diseases and cancer. [5][6][7][8][9][10][11][12] However, to the best of our knowledge, only a few epidemiologic studies have examined the associations between allergic diseases and gastric cancer. One cohort study that analyzed subjects selected from a hospital discharge registry, reported that asthma was associated with reduced gastric cancer risk; 13 however, this study included patients with only severe asthma, and the number of gastric cancer cases was small.…”
Section: Introductionmentioning
confidence: 99%